Is human cytomegalovirus a potential risk factor for mood disorders? A systematic review and meta-analysis - Zahra Yousefian; Seyedeh Masoumeh Seyedhosseini Tamijani; Hamed Ghazvini; Farzan Kheirkhah; Raheleh Rafaiee; Tahoora Mousavi (Indian Journal of Psychiatry)
Mood disorders are among the common mental disorders worldwide. Because of the persistence of cytomegalovirus (CMV) in the body and nervous system, this virus can be activated when the immune system is weakened and continues to exert its destructive effects throughout life. This study aimed to investigate the seroprevalence and association of human cytomegalovirus with mood disorders. Eligible articles were extracted using online international databases Science Direct, Medline, Web of Science, Scopus, and Google Scholar between 2000 and 2023. After quality assessment and specific inclusion and exclusion criteria, a total of eight eligible articles were included in the meta-analysis. Our finding showed that the seropositivity of CMV in mood disorders was 51.6% (95% CI; 42.8–60.4). There were statistical differences between mood disorders and control groups regarding the seropositivity of CMV 1.327% (95% CI; 13.27–10.45). The results of the publication bias using the Egger test confirmed no publication bias in each sub-group. The results of this meta-analysis study demonstrated that CMV infection might have associations with the incidence of mood disorders. Furthermore, we found that there were statistical differences between mood disorders and control groups regarding the seropositivity of CMV.